Microarray‐based identification of human antibodies against Staphylococcus aureus antigens. Issue 11 (1st April 2015) - Kloppot, Peggy; Selle, Martina; Kohler, Christian; Stentzel, Sebastian; Fuchs, Stephan; Liebscher, Volkmar; Müller, Elke; Kale, Devika; Ohlsen, Knut; Bröker, Barbara M.; Zipfel, Peter F.; Kahl, Barbara C.; et al.
Abstract : Purpose: The mortality rate of patients with Staphylococcus aureus infections is alarming and urgently demands new strategies to attenuate the course of these infections or to detect them at earlier stages. Experimental design: To study the adaptive immune response to S. aureus antigens in healthy human volunteers, a protein microarray containing 44 S. aureus proteins was developed using the ArrayStrip platform technology. Results: Testing plasma samples from 15 S. aureus carriers and 15 noncarriers 21 immunogenic S. aureus antigens have been identified. Seven antigens were recognized by antibodies present in at least 60% of the samples, representing the core S. aureus immunome of healthy individuals. S. aureus ‐specific serum immunoglobulin G (IgG) levels were significantly lower in noncarriers than in carriers specifically anti‐IsaA, anti‐SACOL0479, and anti‐SACOL0480 IgGs were found at lower frequencies and quantities. Twenty‐two antigens present on the microarray were encoded by all S. aureus carrier isolates. Nevertheless, the immune system of the carriers was responsive to only eight of them and with different intensities. Conclusion and clinical relevance: The established protein microarray allows a broad profiling of the S. aureus‐ specific antibody response and can be used to identify S. aureus antigens that might serve as vaccines or diagnostic markers.